Protection of Human Rights Against Women in an International Legal Perspective - Kastiady, Salvia Salsabila Putri (International Law Discourse in Southeast Asia, 2024)
Violations of human rights against women are still a serious debate, because there are still many women who experience acts of human rights violations, even though the National Human Rights Commission and the National Women's Commission have been initiated, it is not a guarantee that human rights violations against women will not occur. Sexual violence in international law develops according to the circumstances when acts of violence occur. sexual, where the act of sexual violence occurs. This occurs in conditions of armed conflict or in conditions where there is no armed conflict, namely in domestic life and at work. Sexual violence International law is regulated in many cases, including the Rome Statute of the International Criminal Court of 1974, which classifies sexual violence as the most serious crime. Apart from that, it is also regulated in the general agreement to eliminate all forms of discrimination against women, if the regulations are stricter, preventive measures related to protection against sexual violence are in accordance with this Convention. The National Commission on Violence Against Women has also classified gender-based violence